Productive Zakat and Economic Empowerment: Impact on Mustahiq Income at Darul Ilmi Islamic School - Nurwahidin, Nurwahidin; Islami, Dodik Gilang; Salma, Ria Fauziah; Suyurno, S. Salahudin (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
Despite its substantial zakat potential, economic inequality remains a significant challenge in Indonesia. This study examines the impact of productive zakat on the economic empowerment of mustahiq (zakat recipients) at the Modern Islamic Boarding School Darul Ilmi Indonesia. The research employs a mixed-method approach, combining quantitative income analysis before and after receiving zakat with qualitative insights from beneficiary interviews. The Wilcoxon signed-rank test results indicate a significant increase in mustahiq income post-zakat. This highlights the effectiveness of productive zakat in enhancing economic self-sufficiency. The study's novelty lies in its comprehensive evaluation of zakat's role in socio-economic upliftment within an Islamic educational context. These findings underscore the potential for replicating such models in similar institutions to mitigate economic disparities.